Islamic Financial Engineering : Comparative Study Agreements in Islamic Capital Market in Malaysia and Indonesia - Adhitya Ginanjar (Tazkia Islamic Finance and Business Review, 2013)
Objective –The objective of this paper is to provide a discussion Islamic Financial Engineering which practice between Indonesian Capital Market and Malaysian capital market. This paper also investigate whether regulator could effectively take a role in materializing demands for Islamic securities and whether regulator declaration is more convincing than sharia compliance declaration between IDX and KLSE.Methods - We use descriptive analytic and literature study to see the background, market response caused by regulatory for Islamic Financial Engineering. We also analyze Islamic capital market regulatory from middle east countries.Results - We find that Islamic Capital Market in KLSE (Malaysian Capital Market) more higher growth than IDX (Indonesia Capital Market) because of Islamic Capital Regulatory in KLSE much easier to improve Islamic Financial Engineering from conventional schemes.Conclusion - This finding could explain why Islamic Capital Market in KLSE is still growing rapidly and IDX will adjust their Islamic Capital Market Regulatory to compete with regional Islamic Capital Market.Keywords : Islamic Financial Engineering, Risk, Return, Derivative, Hedging, Option, Forward, Hybrid  contract